Food Web Properties and the Type of Invasive Species Make the Ecosystem Vulnerable to Invasion - Sävilammi, Tiina; Uusi‐Heikkilä, Silva; Kuparinen, Anna (Wiley, 2026)
Invasive species have long been acknowledged as potentially severe dangers to native ecosystems. Although some work has also been done with empirical food webs, more information is still needed to shed light on the cascading effects of invasive species in aquatic ecosystems. In this study, we used an extended niche approach to generate artificial food webs with multiple trophic species and variable parameters. We extended the niche approach by adding several age groups for the top trophic species (fish) to generate food web structures resembling those found in natural environments. Finally, we added an invader species with randomized parameters to each web. We used allometric trophic network (ATN) modelling to simulate 200 years of species biomass changes with and without the invader in the ecosystem. Fish biomasses and old age groups changed the most, with a response that was often a decline in the biomass. The change was predicted by food web depth (the number of feeding levels from the primary producers to the top predators in the ecosystem) and by the magnitude of ecosystem-level changes caused by invasion. Both the properties of native species and the invader, such as the trophic level and direct centrality (specialist/generalist feeding) and indirect centrality (cascading effects), affected the outcome. High Jaccard's similarity between the invader and the native species also predicted a negative impact on the top fish predators.